Acute toxicity profile of three-dimensional conformal concurrent chemoradiation in carcinoma cervix: an institutional experience. Issue 4 (9th December 2020) - Tudu, Rajanigandha; Kumar, Anup; Singh, Rashmi; Raina, Payal
Abstract: Background: Concurrent chemoradiation is the definitive treatment for advanced cervical cancer. Pelvic radiation is known to damage the adjacent normal tissues thereby causing acute toxicities. The modern conformal radiation techniques like three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy are known to reduce the toxicities and improve clinical outcomes. Aim: To retrospectively evaluate the frequency and severity of acute toxicities encountered during concurrent chemoradiation of locally advanced cancer cervix treated with 3D-CRT. Methods: The medical case records of 174 cervical cancer patients treated between November 2015 and November 2018 were studied. One hundred and thirteen histologically proven locally advanced cancer cervix patients (Stage IIB–IIIB) treated with concurrent 3D conformal chemoradiation between were included in the study. Patients received 46 Gy in 23 fractions with concurrent weekly cisplatin (40 mg/m 2 ) on days 1, 8, 15 and 22 of radiation. The study endpoints were treatment-related toxicities which were graded according to CTCAE version 5.0. Results: One hundred and thirteen patients were analysed for the study. Gastrointestinal toxicity was the predominant toxicity observed followed by haematological toxicity. 31·7% patients reported grade 1–2 diarrhoea and 39·7% reported grade 1–2 leucopenia. None of the patients reported grade 3 or higher toxicities. Treatment interruptions were noted due to these toxicities. Conclusion: Concurrent chemoradiation is the definitive treatment for locally advanced carcinoma cervix with acceptable toxicities. Proper management measures should be undertaken for these toxicities to avoid treatment interruptions and ensure better treatment compliance.